Green consumers in the COVID-19 era: What impacts on their consumption? An exploratory study of Moroccan consumers (Economic and Political Thought, 2022)
Climate change and the current major preoccupation with preserving one’s health and body have largely contributed to changing consumer behaviour, which has helped to promote responsible consumption. This consumption has also been influenced by the COVID-19 crisis, which has not only troubled the balance of the economic spheres but has also changed the approach of the green consumption. The objective of this article is to explore the impact of the COVID-19 crisis on the consumption of the Moroccan green consumer through a qualitative study. The study analyses the behaviour of 21 consumers.
Keywords: green consumer, environmental commitment, responsible consumption, COVID-19